Pengaruh Model Pembelajaran Berbasis Masalah terhadap Keterampilan Berpikir Kritis Peserta Didik di SMPN 7 Padang - Oktavia, Rani; Azzahra, Firda; Muttaqiin, Arief; Prima Sari, Monica; Sarmila (SEMESTA: Journal of Science Education and Teaching, 2025)
Observations and interviews with science teachers at SMPN 7 Padang revealed that learning that trains students' critical thinking skills has not been implemented optimally. When students gave answers or asked questions related to the material in science learning, they were still hesitant or limited to understand, also scientific attitude towards science learning. The literature states that Problem Based Learning (PBL) model is able to train students' critical thinking skills. PBL shows effective approach to increase students’ potential and develop students’ critical thinking skills. Therefore, this study was conducted to determine the effect of the Problem Based Learning model on the Critical Thinking Skills of Grade VIII Students at SMP Negeri 7 Padang. This quantitative study used a quasi-experimental design with a pretest-posttest control group design. PBL Model as the independent variable in this study was employed to experimental class, while dependent variable was students’ critical thinking skills tested in both experimental and control class. The measurement of students’ critical thinking skills consisted of five indicators such as elementary clarification, basic support, inference, advance clarification, and strategy and tactics. The results showed a significant increase in students' critical thinking skills in the experimental group compared to the control group (p<0.05). It can be concluded that Problem Based Learning model significantly improve students’ critical thinking skills.